2018
DOI: 10.1152/ajpheart.00235.2018
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal hearts with tetralogy of Fallot have altered fluid dynamics and forces

Abstract: Studies suggested the effect of blood flow forces in pathogenesis and progression of some congenital heart malformations other than the Tetralogy of Fallot (TOF). It is thus of interest to study the fluid mechanic environment of the malformed prenatal heart, especially when little is known in the fetal TOF. In this study, we performed patient-specific ultrasound-based flow simulations of 3 TOF and 7 normal human fetal hearts. TOF right ventricles (RV) had smaller end-diastolic volumes (EDV) but similar stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Accurate estimations of cardiac motion from clinical scans is an important task, and can be used to aid the evaluation of cardiac function 1 , detection of dysfunction in cases such as cardiomyopathy 2 , chemotherapy toxicity 3 and infraction 4 . It has also been used to assist with bio-mechanic studies to understand cardiac physiology based on its experience stress and strain 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Accurate estimations of cardiac motion from clinical scans is an important task, and can be used to aid the evaluation of cardiac function 1 , detection of dysfunction in cases such as cardiomyopathy 2 , chemotherapy toxicity 3 and infraction 4 . It has also been used to assist with bio-mechanic studies to understand cardiac physiology based on its experience stress and strain 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The heart trabeculae is characterized as a ‘spongy’ or porous tissue that develops inside the heart ventricles, and in our samples was evident from semithin transverse heart sections ( Figure 4 ), but could also be approximately quantified as the extracellular portion of the images ( Figure 8 ). It has been shown that the heart trabecular architecture is sensitive to blood flow conditions during development ( Sedmera et al, 1999 ), and thus a disrupted trabecular architecture may be a characteristic of many CHD hearts due to their anomalous flow characteristics during fetal stages ( Wiputra et al, 2018 ). However, the trabecular and myocardial architecture can also exhibit variations from heart to heart ( Gilbert et al, 2007 ), therefore further analysis with a larger sample size is required before we can make conclusions related to TOF.…”
Section: Discussionmentioning
confidence: 99%
“…These hearts were collected at stages corresponding to about 5–6 months of human fetal development, when the heart is already formed but maturing in preparation for birth/hatching. We imaged: (1) a control heart with no structural defects and (2) a heart with tetralogy of Fallot (TOF), a combination of structural heart malformations found in humans ( Bailliard and Anderson, 2009 ; Wiputra et al, 2018 ). Our results show the morphology and ultrastructure of these two hearts, and emphasize the need for a multiscale approach to deepen our understanding of CHD and enable the development of effective strategies to combat heart failure in CHD.…”
Section: Introductionmentioning
confidence: 99%
“…The heart trabeculae is characterized as a “spongy” or porous tissue that develops inside the heart ventricles, and in our samples was evident from semithin transverse heart sections ( Figure 4 ), but could also be approximately quantified as the extracellular portion of the images ( Figure 7 ). It has been shown that the heart trabecular architecture is sensitive to blood flow conditions during development 54 , and thus a disrupted trabecular architecture may be a characteristic of TOF hearts due to their anomalous flow characteristics during fetal stages 18 . However, the trabecular and myocardial architecture can also exhibit variations from heart to heart 11 , therefore further analysis with a larger sample size is required before we can make conclusions related to TOF.…”
Section: Discussionmentioning
confidence: 99%
“…These hearts were collected at stages corresponding to about 5-6 months of human fetal development, when the heart is already formed but maturing in preparation for birth/hatching. We imaged: 1) a control heart with no structural defects; and 2) a heart with tetralogy of Fallot (TOF), a combination of structural heart malformations found in humans 17,18 . Our results suggest differences in the ultrastructure of these two hearts, emphasizing the need for a multiscale approach to deepen our understanding of CHD and enable the development of effective strategies to combat heart failure in CHD.…”
Section: Introductionmentioning
confidence: 99%